Qualitative Analysis of Physics Learning Problems in High School Based on Students' Intrinsic and Extrinsic Factors - Wulandari, Dewi; Riswanto, Riswanto (Universitas Muhammadiyah Purworejo, 2025)
This study aims to analyze the problems in Physics learning at SMAN 1 Punggur. This study is a qualitative research with a grounded theory design focusing on intrinsic and extrinsic factors that influence student understanding. The informants of the study were students and physics teachers at SMAN 1 Punggur. Intrinsic factors include motivation and interest in learning, students' initial abilities, conceptual difficulties, students' practical skills, understanding of abstract concepts, problem-solving skills, collaboration and communication skills. While extrinsic factors include teacher learning strategies, limited facilities and infrastructure, and use of technology in learning. Data collection techniques used in this study were student questionnaires and in-depth interviews with students and teachers. The results of the analysis showed that the problems of physics learning at SMAN 1 Punggur lie in intrinsic factors, namely low motivation and interest in learning, conceptual difficulties, and problem-solving skills.